Superabsorbent polymer prepared using carboxymethyl cellulose derived from Ceiba pentandra (L.) Gaertn. (kapok) cotton. Issue 18 (22nd April 2014) - Khoo, Jennifer Meei Yun; Chee, Swee Yong; Lee, Chee Leong; Nagalingam, Saravanan
ABSTRACT: Superabsorbent polymers (SAPs) were synthesized by grafting acrylic acid and butyl acrylate onto carboxymethyl cellulose (CMC) modified from Ceiba pentandra (L.) Gaertn. (kapok) cotton, with N, N ′‐methylenebisacrylamide as a crosslinker and ammonium persulphate as initiator. The effect of distilled water, saline solution, and applied pressure on superabsorbent was investigated. The product exhibited the maximum water absorbency of 554 g/g in distilled water and 96 g/g in saline solution. The SAP achieved the highest water absorbency under load of 83 g/g under applied pressure of 7.6 g/cm 2 . The kapok cotton modified cellulose‐based SAP exhibited stronger gel strength than the SAP based on commercial CMC. This is probably due to the higher grafting efficiency (78.3%) of the former. The SAP was characterized by FTIR analysis, thermogravimetric analysis, and scanning electron microscopy. Thermogravimetric analysis results showed that the SAP, with AA and BA grafted onto CMC, had better thermal stability than CMC alone. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2014, 131, 40808. Abstract :